LA FRAGMENTADA REGULACIÓN DE LOS VEHÍCULOS DE MOVILIDAD PERSONAL: UN PROBLEMA COMÚN EN PERÚ Y ESPAÑA - González Prada, Carlos; Codina García-Andrade, Xavier (Revista de Derecho, 2020)
The population growth experienced in Peru in recent years has meant a greater demand for basic services, such as transportation. This scenario has led to the emergence of new means of urban transport capable of satisfying new mobility needs, providing efficient and safe access: the so-called personal mobility vehicles. Its sudden incursion, however, has been marred by the proving of a disjointed national and local regulation that threatens its development. In view of this situation, in this article the authors review the objectives in the field of medium and long-term urban transport outlined in the National Urban Transport Policy by the Peruvian Government and the current regulations applicable to personal mobility vehicles, with the object of revealing the inconsistencies currently existing. Subsequently, the authors make some regulatory policy recommendations drawn from the comparative experience, in order to help lay the foundations for their future regulation as a means of sustainable mobility. Among the main recommendations made by the authors, the need to approve a general legal framework, of national scope, that unifies the basic rules of circulation, as well as the desirability of adopting mechanisms that allow its continuous evaluation so that its provisions reflect the provisions International best practices.
Keywords: personal mobility vehicles; urban transport; urban mobility; comparative legislation